3(4-(-5x-7))=105x+159

Simple and best practice solution for 3(4-(-5x-7))=105x+159 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4-(-5x-7))=105x+159 equation:


Simplifying
3(4 + -1(-5x + -7)) = 105x + 159

Reorder the terms:
3(4 + -1(-7 + -5x)) = 105x + 159
3(4 + (-7 * -1 + -5x * -1)) = 105x + 159
3(4 + (7 + 5x)) = 105x + 159

Combine like terms: 4 + 7 = 11
3(11 + 5x) = 105x + 159
(11 * 3 + 5x * 3) = 105x + 159
(33 + 15x) = 105x + 159

Reorder the terms:
33 + 15x = 159 + 105x

Solving
33 + 15x = 159 + 105x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-105x' to each side of the equation.
33 + 15x + -105x = 159 + 105x + -105x

Combine like terms: 15x + -105x = -90x
33 + -90x = 159 + 105x + -105x

Combine like terms: 105x + -105x = 0
33 + -90x = 159 + 0
33 + -90x = 159

Add '-33' to each side of the equation.
33 + -33 + -90x = 159 + -33

Combine like terms: 33 + -33 = 0
0 + -90x = 159 + -33
-90x = 159 + -33

Combine like terms: 159 + -33 = 126
-90x = 126

Divide each side by '-90'.
x = -1.4

Simplifying
x = -1.4

See similar equations:

| 4y(y+3)+y=5+12 | | 8x-3=10x-5 | | -7(t-5)-(t+5)=1 | | 12(b+12)+6=9(b-2)9b | | -ln(x^1/2)-ln(x^1/2) | | 0.35x+0.05(18-x)=0.10(-45) | | 10/3=15/x | | -139=-5(2k+7)-3k | | 49(y+3)+y=5y+12 | | 5x-9=(x-2) | | 7x+8y-16=0 | | 3.00=55b | | 20t+40= | | 120=5(3+x)+2x | | 4a-14= | | C=4x-2y | | 2(4-7)=7u+2-2(-5u-1) | | -12-12(8+5n)=8n+28 | | -16t^2+48t+36=0 | | 13.5-0.3k+2.5-0.8k=7-1.1k-8.4 | | 2x+8-6(x+1)=3x+7 | | 2(6d-3)=6(5+3D) | | y-0=-3(x-2) | | 2[4-(-4x-4)]=64x+72 | | 2a-5(a-2)+4(b-2)= | | a=1/2h(b1b2) | | 2[4-(4x-4)]=64x+72 | | (w-3)(w+1)= | | 2-3(x+4)=9-(3x-2) | | =x^2-2x-11 | | R+0.5=0.7 | | 4+8=6+2t |

Equations solver categories